Louceiras que Burnem: As Representações Matemáticas no Livro Didático e as Práticas Matemáticas na Realidade Quilombola - Silva, Josoel Pereira da (2010)
In this paper I examine two mathematical traditions, one of them is present in the doings, practices and representations of the black (quilombola) community from Irará, whose main activity is the production of pottery ware, made through knowledge passed from parents to children, another tradition is in textbooks used in schools that deal with this community. The specific focus is the geometric knowledge present at everyday situations in black community, buildings, uses and consumption of various types of objects and products, from utensils until artistic production, getting through food and comparing them with the geometric knowledge present in textbooks. The survey covered two moments; the first one comprises the day-to-day in that community, its knowledge and practices, characterized by the making of pottery, which develops itself from the removal of mud, getting through production of parts, until getting through its marketing. The second one corresponds to the daily school community members, showing that the examples and illustrations of geometric shapes present in the textbook are not related to the mathematical activities developed in the black community, contributing thereby to be neglected the practices and representations of its daily.